SIMETRI DALAM TIR & LIR KARYA MARIE REDONNET - masdiana, Masdiana; Yolanda, Ade; Sarro, Sitti Fhatimah (Universitas Hasanuddin, 2016)
The purpose of this research is to know the symmetry extension that can be observed in the use of the domain literature (a piece theater). This study was analyzed using structuralism approach (the intrinsic elements of theater and the technical presentation story within a story – “frame story”). Furthermore, the interpretation of the image of the French family (intergenerational today) and the interpretation of the words, actions, setting and other is then adapted to the symmetry model. Finally, the idea of symmetry that explain their influence the presentation of the literary work. The results of the research is to know that the symmetry is used to advance the things aligned, balanced and orderly, so that the work is in accordance with the concept of the primordial beauty of the west. As something that is wrapped by the beauty will interest faster for people to know more about what is contained in it.